UJI STATISTIK PADA PENELITlAN PENGARUH PERLAKUAN PERMUKAAN TERHADAP UMUR FATIK DENGAN DATA TERBATAS - Suhartono, H. Agus (Program Studi Teknik Mesin, Universitas Trisakti, 2006)
Justifications on the influences of two or more parameters on fatigue strength are some timesproblematic due to the nature scatter of the fatigue data. Statistic test canfacilitate the evaluation, wether thechanges in material characteristics as a result ofspecific parameters of interest is significant. Thestatistictests were applied tofatigue data ofAISI 1045 steel specimens. Thespecimens are consisted ofas receivedspecimen, shotpeenedspecimen with 0,0147 and0,0161 Almen intensity as well as carburizedspecimen. Thefatigue tests of the specimens are conducted in three horizonts of loading. The fatigue datas are thendescribed by S-N diagrams (Stress - Cycles to Failure diagrams). A transformation to one stress horizon iscarriedout dueto limitedamount ofthefatigue data. Statistic tests, which are appliedto the datasshow, thattheshotpeeningandcarburization processprovide a significant effect to thefatigue strength ofthespecimen.However additional timein shotpeeningprocess with thepurposeofincreasing theshotpeening intensity hasnosignificant effectto the increasingoffatigue strength ofthesteel specimens.